Fibroblast growth factor 23 and lipid metabolism association in chronic kidney disease - M. I. Chaikovska; L. P. Martynyuk (Ukrainian Journal of Nephrology and Dialysis, 2018)
Recent scientificstudies have demonstrated the effect of fibroblast growth factor 23 (FGF-23) on the volume and distribution of body fat. The aim of our study was to investigate of lipid metabolism in patients with chronic kidney disease (CKD) and its relationship with FGF-23.Methods. We conducted a single-center, cohort retrospective study involved 106 patients with CKD 1-5 stages. Among the patients were 47 women (44%) and 59 men (56%) aged (49.6±13.9) years. All patients were determined the blood lipid spectrum: total cholesterol level (LDL), high density lipoproteins (HDL) and triglycerides (TG). The lipid profile was examined using a biochemical analyzer Cobas Integra 400 Plus. The C-terminal FGF-23 fragment was determined using a set of reagents for the enzyme immunoassay “Biomedica” (Astria). The glomerular filtration rate (GFR) was calculated using the CKD EPI formula (KDIGO 2012). All the statistical analyses were performed using Statistica 10.0.Results. In patients with CKD, progressive decrease in the level of total cholesterol, LDL cholesterol, HDL cholesterol and the increase in TG concurrent with the fall in GFR was detected (p<0.001). The concentration of the C-terminal FGF-23 fragment progressively increased in parallel with the fall in GFR, reaching the highest values at CKD stage 5 (p<0.001). A significant relationship was found between FGF-23 and total cholesterol (r =-0.45, p<0.05), LDL (r=-0.29, p<0.05), HDL (r=-0.54, p<0.05), FGF-23 and TG (r=0.28, p<0.05).Conclusions. CKD is characterized by a significant growth in TG levels, which increases with progression of renal dysfunction. The level of FGF-23 in CKD steadily increases in parallel with the decrease in GFR. The parameters of lipid metabolism, namely, total cholesterol, LDL, TG and HDL, have a reliable relationship with FGF-23 in CKD.